Omphalitis Leading to Retroperitoneal Abscess in a Neonate: A Case Report - Orozco Hernández, Juan Pablo; Mesa-Tobón, Laura María; Mesa-Franco, Jaime Alberto; Vinasco- Sánchez, Luis Gabriel (Journal of Neonatal Surgery, 2019)
Retroperitoneal abscess in neonates is extremely rare and can be fatal in case of late diagnosis. A 7-day-old newborn presented with irritability, fever, lethargy, periumbilical erythema, and a tender abdominal mass. The initial laboratory findings were a high c-reactive protein, and respiratory alkalosis. An emergent laparotomy was performed revealing a retroperitoneal abscess that required drainage. The only etiology identified in the patient was omphalitis.